Abordando o ensino de eletrostática através da construção do gerador de Van de Graaff - Jesus, Gerson de (2021)
This Master's dissertation has as main objective to describe the experimental practice, using the electrostatic generator, built with alternative material and of low cost, as pedagogical tool in the teaching learning of the contents of the electrostatic. This work was applied in a State School of the State of Goiás, with 23 students of the third grade of high school. The purpose of the dissertation was to provide an attractive teaching, based on the experimental act, using it as a motivational means in the assimilation of knowledge. The research addresses the literature review, making reference to the teaching of physics and pedagogical practice. The application of the product contributes significantly to the understanding of the concepts of electrostatics, such as: The history of electricity, electric charge, electrification processes, conductors and insulators, electric force, electric field and electric potential. The components of the generator will be presented, highlighting its operation, application and results, in addition to showing the process of assembling a model made from materials that are easy to obtain and of low cost. Based on the contents of electrostatics, proposals for activities and their possible approaches with the generator were elaborated. This work does not focus on evaluating the effectiveness of the resource, but on providing an alternative to the teacher in the classroom.